Evaluation of the psychometric properties of the Military Suicide Attitude Questionnaire (MSAQ) among conscripts of the Islamic Republic of Iran Army Ground Forces deployed in Shiraz in 2020 - Sajjad Ghaedian; Hassan Shahmiri; Arsia Taghva; Haleh Shahed-Hagh Ghadam; Shayan Kashefinejad; Zahra Sadat Asadi; Naser Goudarzi; Vahid Donyavi; Melika Salmani; Amir Mohsen Rahnejat (فصلنامه ابن سینا)
Background and aims: Understanding the attitudes of military personnel towards suicide is crucial for evaluating suicide prevention programs, clinical practices, and policies within the military community. This study aimed to assess the psychometric properties of the Military Suicide Attitudes Questionnaire (MSAQ) among conscripts in the Islamic Republic of Iran Army Ground Forces. Methods: In 2020, a descriptive-correlational study was conducted with a sample of 420 conscripts selected through cluster sampling. Data were collected using a demographic information form, the MSAQ, Suicide Stigma Scale (SOSS), and Beck Scale for Suicidal Ideation (BSSI). Face validity was determined qualitatively, internal consistency was assessed using Cronbach's alpha, and convergent, divergent, and retest validity were evaluated using Pearson correlation coefficient. Exploratory factor analysis was employed to identify the MSAQ's factor structure. Results: Analysis revealed that the MSAQ showed convergent validity with the SOSS and divergent validity with the BSSI. The questionnaire demonstrated appropriate internal consistency, test-retest reliability, concurrent validity, and cut-off point. Conclusion: The findings suggest that the MSAQ is a valid and reliable tool for assessing suicidal ideation among conscripts in Iran.